"Green" performance measurement. (11th May 2004) - Andersen, Bjorn; Fagerhaug, Tom
This paper attempts to: demonstrate that environmental impact constitutes part of an enterprise's competitiveness; convince the reader of the necessity for monitoring environmental impact; and outline how an enterprise can design a green performance measurement system. The argument about the importance of environmental friendliness as a source of competitiveness is based on general trends in society. This is followed by an overview of the development of modern performance measurement systems, showing that while these have also started to incorporate the environmental dimension, it has not been covered sufficiently well. Simultaneously, a number of references show that there is a clear need for environmental monitoring, both at a national and enterprise level. The suggested green performance measurement approach is based on measurements at three levels, strategic, tactical, and operational. For each of these, performance indicators are suggested which should help an enterprise advance in the right direction.